Sistem Pengolahan Air Laut Menjadi Air Minum Menggunakan Tenaga Matahari - Iswadi Iswadi; Aisyah Aisyah (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2013)
Has done research about the system of purification of sea water into drinking water using solar energy. Utilization of solar energy as power naturally adopts the system of evaporation that occurs in a siklur water. Design and construction of tools created in the shape of a pyramid so that the absorption of thermal energy from the Sun can be maximum. Methods of work of the system is very simple, namely the souls imprisoned in the air that the pyramid would experience an increase in temperature significantly along with the searing Sun. The temperature of the hot air in the space pyramid is causing sea water which is at the bottom (floor) pyramid will evaporate and stick on the wall side of the inside of the pyramid. With the help of gravity, the water vapour will fall in the form of green ears water down the wall of the pyramid. The water will flow through the channel leading into the shelter is. This water is not already contain salt and pure water is so that it can be consumed directly. The results showed that the pyramid with size 160 cm x 160 cm 3 mm fiberglass-wall capable of producing fresh water as much as 2,100 mL. These results have been tested in the laboratory with a result salinity = 0,0 at T = 29,4 °C; TDS = 11 mg/L, 22.2 ms/cm conductivity, at T = 29.3 °C, no taste and no smell.